Procrastination: a bibliometric analysis of the past decade (Research, Society and Development, 2022)
This bibliometric study aims to analyze the scientific production on the theme Procrastination, in the Web of Science (WoS) and Scopus (CAPES, 2020) databases. This research is characterized with a descriptive nature, quantitative approach and application of bibliometric analysis. Using the “procrastination” theme, searches were limited from 2009 to December 2020. The analysis considered the following elements: time evolution, total number of publications, thematic area, type of document, countries, main authors and report of quote. As a method for data analysis, the VOSviewer system was used to create textual maps, co-citation clusters and keywords. The results of the research show that the topic is opportune, since the topic has grown significantly over the years and the publications in the two databases, Scopus and WoS, are concentrated in the United States. It should also be noted that the area that most researches on procrastination is Psychology and the type of publication with the largest amount is in the format of a scientific article. As a limitation of the study, the realization in only two databases stands out. It is suggested for future studies, that the sample be extended to include academic, national and international events, journals, as well as other scientific databases.